2016
DOI: 10.1016/j.compositesa.2016.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of moisture uptake on the static, cyclic and dynamic behaviour of unidirectional flax fibre-reinforced epoxy laminates

Abstract: International audienceThis papers aims to characterize the influence of moisture uptake on the mechanical behaviour of unidirectional flax fibre-reinforced epoxy laminates. Monotonic and cyclic tensile tests and free vibration characterization are carried out. Results show that LID flax-epoxy composites, when exposed to hygrothermal conditioning at 70 degrees C and 85% RH, exhibit a diffusion kinetic which follows a one dimensional Fickian behaviour. The mass uptake at equilibrium is approximately 3.3% and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 57 publications
7
76
2
Order By: Relevance
“…(4) The best fit is obtained with a logarithmic law. The identified  parameter is lower when compared to the value obtained by Bergès et al [4] (17 vs. 20) on a quasi-UD flax-epoxy composite, traducing a better resistance to fatigue. Indeed, the fatigue strength for 10 6 cycles is approximately 200 MPa.…”
Section: Influence Of Speed On the Monotonic Tensile Behaviourcontrasting
confidence: 72%
See 3 more Smart Citations
“…(4) The best fit is obtained with a logarithmic law. The identified  parameter is lower when compared to the value obtained by Bergès et al [4] (17 vs. 20) on a quasi-UD flax-epoxy composite, traducing a better resistance to fatigue. Indeed, the fatigue strength for 10 6 cycles is approximately 200 MPa.…”
Section: Influence Of Speed On the Monotonic Tensile Behaviourcontrasting
confidence: 72%
“…The material clearly exhibits a nonlinear behaviour and more exactly a bi-phasic behaviour. The nonlinearity is now well-accepted and documented for flax-epoxy composites [2,4,40,41]. For the tape-based material tested in this study, the modulus-strain curve (see Fig.…”
Section: Monotonic Tensile Behaviourmentioning
confidence: 63%
See 2 more Smart Citations
“…Another issue that contributes to a great extent to the low aging resistance of NFRPs under humid environmental conditions is the poor compatibility between hydrophilic natural fibers and several hydrophobic polymeric matrices such as epoxy resins [30,31]. In this regard, some researchers showed that the water resistance of natural fiber-reinforced polymer composites can be improved and their quasi-static mechanical properties under humid environment can be better retained through fiber chemical treatments [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%